Early Introduction of Solid Foods in Infant’s Nutrition and Long-Term Effects on Childhood: A Systematic Review - Antoniou, Evangelia; Dagla, Maria; Iliadou, Maria; Palaska, Ermioni; OROVOU, EIRINI (International Journal of Innovative Research in Medical Science, 2022)
Background: Early solid food introduction in infancy has been related with some long-term outcomes in childhood, such as high BMI, obesity, diabetes type 1, feeding difficulties andF2-isoprostanes in urinary. Methods: The purpose of this systematic review is to provide the long-term effects of the early introduction of complementary foods in childhood, independently of breastfeeding or formula-feeding. Methods: Twelve research studies from Google Scholar, PubMed, and Crossref were added in the systematic review from a total of 1517 articles. Results: Most studies have shown an association between the introductions of solids before 4 months of age and long-term outcomes in children. However, late introduction of solids may have the same effects as early. Moreover, the role of breastfeeding, which acts protectively in the food transition, is emphasized. Conclusions: The most appropriate age for introduction in solids is the period of 6 months with continued breastfeeding according to the international guidelines.